Anticipatory evolution and DNA shuffling - Bacher, Jamie M (BioMed Central, 2002)
DNA shuffling has proven to be a powerful technique for the directed evolution of proteins. A mix of theoretical and applied research has now provided insights into how recombination can be guided to more efficiently generate proteins and even organisms with altered functions.